Investigation of the Kinetics of Heat and Moisture Exchange during Heat Treatment and Drying of Thin Wet Thermal Insulation Materials - A. I. Ol’shanskii; A. N. Golubev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
. The kinetics of drying of thin heat-insulating flat materials has been studied. The approximation of the drying rate curve by various methods is presented. When determining the duration of drying by zonal methods, the equation of the drying rate with the drying coefficient was used. The techniques of processing experimental data by zonal methods of A.V. Lykov, V. V. Krasnikov and by the method of B. S. Sazhin are described. The equation obtained by processing experimental data using the B. S. Sazhin method to determine the duration of the drying process contains only the amount of moisture content of the heating of the material, there is no need to know the critical moisture content. Dependences for calculating the drying coefficient by zonal methods are given. According to the results of the experiment, formulas for determining the duration of heat treatment of thermal insulation materials are presented. The dependence of the relative drying rate on the relative moisture content is presented as well. The processing of experimental data by generalized complex variables creates invariance conditions that allow moving from one variable to another, from one coordinate system to another, which reduces the number of experiments. Formulas with complex variables for determining the duration of drying of materials are given. Based on the drying kinetics equation by A. V. Lykov and the equation for the relative drying rate by G. K. Filonenko, equations are given for determining the density of heat fluxes, the intensity of moisture evaporation and temperature for the period of decreasing drying rate. Solutions of experimental equations are analyzed. The error caused by the processing of experimental data is established. Verification of the reliability of the empirical equations obtained is presented and comparison of the calculated values of the main parameters of the drying kinetics with the experiment is carried out.